2012
DOI: 10.1128/jvi.01675-12
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the Adeno-Associated Virus Assembly-Activating Protein

Abstract: b Adeno-associated virus (AAV) capsid assembly requires expression of the assembly-activating protein (AAP) together with capsid proteins VP1, VP2, and VP3. AAP is encoded by an alternative open reading frame of the cap gene. Sequence analysis and site-directed mutagenesis revealed that AAP contains two hydrophobic domains in the N-terminal part of the molecule that are essential for its assembly-promoting activity. Mutation of these sequences reduced the interaction of AAP with the capsid proteins. Deletions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
75
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 26 publications
5
75
0
Order By: Relevance
“…In keeping with this notion, mutations in this region could substantially reduce AAP2 protein levels without affecting its intracellular localization and could result in significantly impaired capsid assembly (AAP2mt8, -mt9, and -mt10). The reduction of capsid production by an AAP2BR1 mutation has also been reported by Naumer et al (1). Although the mechanism for the decreased protein expression has yet to be determined, it could be either due to intrinsic instability caused by protein misfolding or due to decreased protein-protein or protein-nucleic-acid interactions that stabilize AAP2.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In keeping with this notion, mutations in this region could substantially reduce AAP2 protein levels without affecting its intracellular localization and could result in significantly impaired capsid assembly (AAP2mt8, -mt9, and -mt10). The reduction of capsid production by an AAP2BR1 mutation has also been reported by Naumer et al (1). Although the mechanism for the decreased protein expression has yet to be determined, it could be either due to intrinsic instability caused by protein misfolding or due to decreased protein-protein or protein-nucleic-acid interactions that stabilize AAP2.…”
Section: Discussionmentioning
confidence: 74%
“…Recently, a nonstructural viral protein encoded by an alternative ORF within the cap gene was identified and termed assembly-activating protein (AAP) for its indispensable role in capsid formation (1)(2)(3). The AAP (AAP2) from AAV serotype 2 (AAV2) is a nucleolar-localizing protein that binds to VP proteins through interacting domains in the amino (N) terminus of AAP2 (1), transports the VP proteins to the nucleolus, and promotes capsid assembly (3). Therefore, AAP2 is expected to have both a nuclear localization signal (NLS) and a nucleolar localization signal (NoLS) within its protein sequence.…”
mentioning
confidence: 99%
“…A total of 60 copies of the three VPs, in a ratio of 1:1:8 to 10 (for VP1:VP2:VP3, respectively) based on gel densitometry (35,36), assemble the Tϭ1 icosahedral particle (37). A third alternative ORF, in the VP2/VP3 mRNA, which encodes an assembly-activating protein reported to aid capsid assembly, was recently discovered (38). It is believed that during cellular entry by AAV capsids, exposure to acidic conditions in endosomes leads to a conformational change and exposure of the VP1u and VP1/2 common regions required for endosomal escape and nuclear entry (34).…”
mentioning
confidence: 99%
“…Genotoxic or cytotoxic factors such as SV40 large T antigen (LTAg) that transformed or altered a cell cycle have also been shown to support AAV replication and assembly (Nicolas et al, 2012). It has been reported that total HeLa cell proteins and DNA helicase are required for AAV assembly (Steinbach et al, 1997;King et al, 2001;Sonntag et al, 2011;Naumer et al, 2012). A recent report using proteomics analysis of AAV vectors showed the association of 10 cellular proteins, for example, Nucleolin (NCL) and nucleophosmin (NPM1), with AAV vectors (Dong et al, 2014).…”
Section: Introductionmentioning
confidence: 99%